PENGARUH PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN TERBUKA DI INDONESIA - Rizki Ardian; Muhamad Syahputra; Deris Desmawan (FEB Universitas Maritim Semarang, 2022)
Abstract. Indonesia's economic growth and open-air unemployment rates need to be discussed whether they have an impact or not. Free variables which are economic growth and bound variables are open unemployment. The research method used is quantitative method using document data from the statistical central body (BPS) in Indonesia. Research has shown that economic growth has not hada significant impact on open unemployment. . Where if there is an increase in economic growth it is not certain that it will reduce the open unemployment rate in Indonesia